Prevalence of Inter Arm Blood Pressure Difference among Type 2 Diabetics in Primary Care - Balushi, Dr. Amal Al; Jahan, Dr Firdous; Jahdhami, Dr. Maiya Al; Bhargava, Dr. Kamlesh (International Journal of Innovative Research in Medical Science, 2018)
Hypertension in patients with diabetes is a common problem; it increases the risk of cardiovascular, renal and ophthalmologic complications. Appropriate measurement of blood pressure is important, as the readings are the target of all pharmacological and non-pharmacological treatment. The aim of the present study was to observe the prev-alence of significant difference in blood pressure in the arms in type 2 Diabetics and to establish if there is association between inter-arm blood pressure difference (IAD) and cardiovascular risk. A cross sectional study conducted in 5 primary care health centers. BP measurements were done by automatic Omron 7 machine; the measure-ments were done two times with interchanging the instruments between two arms. Da-ta collection included demographic data (including, age, sex, body mass index (BMI), waist circumferences, duration of Diabetes, history of HTN, and smoking status).The data collection form also included entry of last biochemical investigations done in-cluding total cholesterol, LDL, HDL, triglyceride, glycosylated hemoglobin (HbA1c) and Cardiovascular risk (CV risk ) calculated by UKPDS engine version 2.0. Data was analyzed with SPSS (version 19). A total of 155 patients were studied. Mean age of patients was 55yrs. 22 participants (14.2, 95% CI=9.1-20.7) had systolic IAD >10 mmHg, 51 (33%, 95% CI=25.6-40.9) had a diastolic IAD >5 mmHg and 9 (5.8 %, 95% CI=2.7-10.7) had a diastolic difference >10 mmHg. In addition, the results showed statistically significant correlation between systolic interarm BP difference and duration of diabetes (P=0.025).There is significant diastolic interarm blood pres-sure difference in diabetic patients. Hence it is important to measure the blood pres-sure in both arms for patients with diabetes to treat hypertension in diabetics appropri-ately.